Un point de généalogie sur deux orfèvres parisiens du XIXe siècle : les « Favier » orfèvres parisiens de grosserie - Claude Aliquot (In Situ)
A departmental order of the Executive Directory, signed on 21 Brumaire Year V (11 November 1796) instructed craftsmen working with precious metals to inscribe their new proof-mark on a copper plate table held in the offices of the administration. This proof-mark, designed to identify the silver or gold smith was to be in the shape of a lozenge but its contents were left to the diligence of the smith. It was supposedly struck off the record when the craftsman ceased operations, but this was not necessarily the case, as our examination of the production of the Favier workshop demonstrates.